DISKURSUS AKHLAK DALAM FILSAFAT MULLA SADRA - Thuba Kermani; Muhammad Nur (Kanz Philosophia: A Journal for Islamic Philosophy and Mysticism, 2014)
In Mulla Sadra’s system of thought, the discussion of philosophy of moral (ethics), morality, the nature of morality and matters related, that is the soul (nafs) and the spirit, is not a short discussion. All forms of action and the nature of malakah imprinted in the human psyche that will participate in the world hereafter. Therefore, some of the matters of the soul is a postulate of science of moral. Yet despite the differences in the ethics’s school of thoughts, it can be said that almost Muslim philosophers agree to the connection of moral with the perfection of soul. And the foundation of moral questions rests on the principle of perfection of the soul and the effects of the moral act. Without them, there will be no perfect rational and philosophical explanations of the good and bad character. However, in understanding how the process of perfection of the soul through moral acts, it is necessary to understand the perfection of the soul and make it a goal for human.